Stretched-pulse fiber laser mode-locked by PbS quantum dots. (July 2022) - Cui, Han; Zhang, Hancheng; Ding, Chen; Ding, Yongqi; Ju, Yi; Ma, Xiaoqing; Lu, Dengyun; Yun, Ling; Yu, Kehan; Wei, Wei
Highlights: The 550-fs stretching pulse was experimentally demonstrated in a PbS quantum dot mode-locked erbium-doped fiber laser for the first time. High modulation depth of about 43.87%. High thermal damage threshold>38 mJ/cm 2 . The formation and dynamic evolution of the stretched-pulse under numerical simulation are in good agreement with the experimental observations. Abstract: Using PbS quantum dots (QDs) as a saturable absorber (SA), ultrafast stretched-pulse are generated in a passively mode-locked erbium-doped fiber laser at near-zero dispersion. Owing to dispersion management, the laser can generate pulses with a duration of 550 fs and a bandwidth of 8.8 nm at a repetition rate of 9.18 MHz. The modulation depth of the SA prepared by dropping PbS QDs on the end face of the optical fiber connector can reach 43.87%. To the best of our knowledge, this is the first report on a stretched-pulse fiber laser based on PbS QDs mode locker. Numerical simulations are performed to investigate cavity dynamics, and obtained results are consistent with experiment.